The Employee Performance Model of Indonesia Sharia Bank Gresik Branch - Malik, Ahmad Dahlan; Muhammad Asyhad; Wahyu Agung Handono (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
The development of Islamic banks in Indonesia is not only focused on increasing the development of the number of assets, financing channeled, third-party funds, but process side, namely to human resources related to the performance of Islamic bank employees. The need for in-depth studies related to employee performance where this research is aimed the relationship of factors supporting the performance of Indonesian sharia bank employees branch in the form of Religiousness, discipline, communication, employee relationship management, interpersonal communication, incentives, training, and work pressure. This research uses quantitative methodology with Structural Equational Modeling (SEM) analysis with the aim of knowing the relationship and the right model on the development of the performance of Indonesian Sharia Bank employees. The results of this study indicate that the variables of discipline, communication, employee relationship management, and religiosity have a significant relationship on employee performance while the other variables do not have a significant relationship